Aspects of work and sleep associated with work ability in regular aviation pilots - Pollyanna Pellegrino; Elaine Cristina Marqueze (Universidade de São Paulo, 2019)
ABSTRACT OBJECTIVE: Analyze the association of work organization and sleep aspects with work ability in regular aviation pilots. METHODS: This is a cross-sectional epidemiological study with 1,234 regular aviation pilots who worked domestic and international flights, affiliated with the Brazilian Association of Civil Aviation Pilots. Data collection employed online questionnaire. We compared proportions using Pearson's Chi-squared or Fisher's exact hypothesis tests. Then, we conducted Poisson analysis, with robust variance, to test factors associated with moderate or low work ability. RESULTS: The prevalence of moderate or low work ability was 43.3%. We found that self-perception of insufficient sleep (PR = 1.29; 95%CI 1.06-1.57), increased perception for fatigue (PR = 1.51; 95%CI 1.24-1.84), more than 65 flight hours per month (PR = 1.22; 95%CI 1.01-1.46), less than 10 days of time off per month (PR = 1.27; 95%CI 1.04-1.55), and frequent operational delays (PR = 1.23; 95%CI 1.02-1.48) were factors associated with moderate or low work ability. CONCLUSIONS: Work organization was a determining factor for decreased work ability, especially concerning aspects related to rest and its influence on the sleep of pilots.